Effect of different downstream temperatures on the performance of a two-layer porous burner - Hayashi, Thamy C. (2010)
The influence of considering different downstream temperatures on the performance of a two-layer porous burner is studied numerically. A 3D numerical model based on a unit cell was implemented to correctly predict the momentum, heat and mass transfer at the interface of the two layers. Two operating modes are simulated corresponding to the burner radiating to cold and hot environments. When the burner radiates to a hot environment, its radiative heat losses are lower and, as a consequence, the temperatures and pollutants emissions are higher. Additionally, the flame front moves upstream and stabilizes nearer the interface of the two layers.